2019
DOI: 10.1371/journal.pone.0213668
|View full text |Cite|
|
Sign up to set email alerts
|

Testing the decoy effect to increase interest in colorectal cancer screening

Abstract: Literature on consumer choice has demonstrated that the inclusion of an inferior alternative choice (decoy) can increase interest in a target product or action. In two online studies, we tested the impact of decoys on the probability of previous non-intenders to have a screening test which could significantly lower their chances of dying of colorectal cancer. We find that the presence of a decoy increased the probability to choose screening at the target hospital (over no screening) from 39% to 54% and 37% to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 44 publications
(45 reference statements)
1
30
0
Order By: Relevance
“…With regards to numeracy, it was important to note that only 55% of responders answered the numeracy question correctly; this was in line with a previous study using a comparable sample of UK adults in a similar age range, 28 which may have to do with specific characteristics of the sample population. However, it also demonstrates the need to review specifically the way that information about risk (often presented in numerical form) is communicated to the public.…”
Section: Discussion Summarysupporting
confidence: 85%
“…With regards to numeracy, it was important to note that only 55% of responders answered the numeracy question correctly; this was in line with a previous study using a comparable sample of UK adults in a similar age range, 28 which may have to do with specific characteristics of the sample population. However, it also demonstrates the need to review specifically the way that information about risk (often presented in numerical form) is communicated to the public.…”
Section: Discussion Summarysupporting
confidence: 85%
“…Furthermore, we followed their approach to present eligible participants with a short description of flexible sigmoidoscopy, which is offered in England at no cost to men and women aged 55, and then asked them to correctly identify where the scope is inserted (to ensure they had read and understood the description of the screening test). Participants were not able to continue with the survey unless they could correctly answer the comprehension question (Stoffel et al, 2018;von Wagner et al, 2019). Participants were then asked to indicate their intention to undergo flexible sigmoidoscopy screening using the question: 'Would you take up the offer if you were invited to have the bowel scope screening test?'…”
Section: Methodsmentioning
confidence: 99%
“…Only 309 women (27.7%) indicated that they would 'definitely not' (N=56) or 'probably not' (N=219) do the test and were therefore considered 'disinclined' and randomised to one of the two experimental conditions with equal probability. We chose to test the decoy among disinclined people to minimise ceiling and social desirability effects often associated with self-reported intention measures (Michie & Abraham, 2004) and to simulate a targeted intervention aimed at non-attenders who are in most need of an effective behavioural intervention (Stoffel et al, 2018;Stoffel et al, 2019;von Wagner et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations